Infantile Cortical Hyperostosis: Report of a Case with Observations on Clinical Manifestations, Radiology, and Pathology with a Late Follow-Up of Eight Years - Pedro Carlos M. Sarmento Pinheiro; Ierecê Lins Aymore; Armando Rocha Amoedo; Paulo Miguel Hemais (Case Reports in Pediatrics)
Purpose. The purpose of our study was to investigate clinical manifestations, roentgen images, histopathological studies, and evolution of the disease in patient displaying infantile cortical hyperostosis. Methods. Roentgenograms were made to evaluate a neonatal patient presenting multiple soft-tissue swellings. The initial radiographs insinuated that the disease had been present for some time in utero. Bone puncture biopsy of the tibia for histopathological observation and diagnosis conclusions was performed. Results. The disease was demonstrated radiographically by massive cortical diaphyseal thickening and also extensive periosteal new bone formation surrounding several bones. Results in blood count were as follows: discrete anemia, moderate leukocytosis, and elevated sedimentation rate. Histological pattern of tissue removed from tibia showed lamellar cortical bones and hyperplasia. Biopsy studies disclosed no evidence of neoplasia as well as of bacterial infection. Comments. Clinical manifestations in a neonatal patient displaying infantile cortical hyperostosis have gradually decreased. Radiograph findings have demonstrated complete recovery of bones manifested by the disease. The pathologic findings are in accordance with previous microscopic examination summarized by the literature. Total patient cure, without sequels, could be demonstrated.